Permanent education in the Hospital Emergency Service: Prior note (Research, Society and Development, 2020)
This study aims to inform about a research that investigates the understanding of health professionals about the educational actions developed for the work process in a public hospital emergency in a city in Rio de Janeiro, in addition to building strategies, as a team, aiming institutionalize the Center for Permanent Health Education. This is a qualitative, descriptive, exploratory study, of the Convergent Care Research type with hospital emergency professionals. Data collection was divided into two stages, one through a semi-structured questionnaire and the other through workshops with active methodologies. The information will be treated through the analysis of Bardin, at the light of the National Policy of Permanent Education in Health in line with Emerson Merhy's theory of live work in action. It is expected to promote the reflection of the importance of Permanent Education, turned and focused on the organization of work processes in the emergency sector and its contribution to the professionals’ meaningful and committed with the real needs of the population.